154k views
4 votes
Substitute x with (-2) and y with (-4)
Simplify: 5(41 - x) + {-7(y + x)} =

User Tauras
by
4.8k points

2 Answers

3 votes

Answer:

257

Explanation:

5(41-(-2))+{-7(-4-2)}

5(41+2)+{-7(-6)}

5(43)+(42)

215+42

257

User Emer
by
5.1k points
1 vote

Answer:

The value which is obtained on simplifying the expression is:


257

Explanation:

We are asked to simplify the expression which is given in terms of two variables x and y as follows:


5(41-x)+(-7(y+x))

Now, we have to simplify the expression for the values of x and y as follows:


x=-2\ and\ y=-4

On putting these values in the given expression:


5(41-(-2))+(-7(-4-2))\\\\=5(41+2)+(-7* -6)\\\\=5* 43+42\\\\=215+42\\\\=257

User Bwall
by
4.8k points